Determining the Infectious Pathogens and Their Resistance to Antibiotics in a Pediatric Intensive Care Unit - Akın, Fatih; Yazar, Abdullah; Doğan, Metin (Journal of Pediatric Infectious Diseases, 2018)
Introduction Nosocomial infections are one of the main causes of morbidity and mortality. It is important to know the common infectious pathogens and their resistance profiles in intensive care units (ICUs) to determine appropriate treatment protocols. The aim of this study was to determine the epidemiological profile of microorganisms isolated in a pediatric ICU (PICU) and to determine antibiotic resistance in isolated strains.Materials and Methods This retrospective study was performed at the Meram Medical Faculty Hospital, Necmettin Erbakan University, Konya, Turkey. A total of 1,502 bacteria that were isolated from various specimens from children who were hospitalized in PICUs between January 2014 and December 2015 were included in this study to determine the isolated bacteria diversity and susceptibility to various antibiotics.Results Staphylococcus spp. was the most frequently isolated microorganism followed by Escherichia coli and Klebsiella spp., respectively. The sites where pathogens were isolated were as follows: 616 blood, (41%), 445 urine (29.6%), 60 sputum (4%), 44 cerebrospinal fluid (2.9%), 25 wound swab (1.6%), 20 tracheal aspirate (1.3%), and 26 others (1.7%). The carbapenem resistance rate was 40.8% among Pseudomonas aeruginosa isolates. Among 60 Acinetobacter baumannii isolates tested, 62% were resistant to carbapenems. Sensitivity rates of A. baumannii isolates to tigecycline and colistin were as high as 98 and 96%, respectively. Meropenem and colistin resistance rates to Klebsiella spp. were 16.2 and 15%, respectively.Conclusion In conclusion, it is essential to identify the infectious pathogens and their resistance to antibiotics especially in ICUs where infections with multidrug-resistant bacteria are frequent. Studies on this issue should be performed at appropriate time intervals.
Keywords: pediatric intensive care unit; infection; resistance rates